PERANCANGAN SISTEM INFORMASI PENERIMAAN SISWA BARU PADA SMK NEGERI I ALLA KABUPATEN ENREKANG - Nurnaningsih Nurnaningsih (AkMen JURNAL ILMIAH, 2008)
In mengolah of new student acceptance information of SMK Neg. 1 Alla still use the manual system (using new student acceptance book). This matter generate various weakness, for example : arrangement inefficient data organization, requiring sufficient time in conducting sequence assess the Danem, its his make the student report expressed by pass the selection